Economic, Social, Cultural Capital of the Region of Puno, Peru - Barra-Quispe , David Eleazar; Mamani-Flores, Adderly; Ticona-Yanqui , José Luis; Ferro-Supo , Francis Walter; Chura-Flores, Juan Carlos; Huanacuni-Zapana, Tony Henry; Ccori-Valdivia, Dimaz (Journal of Ecohumanism, 2024)
The present research had the need to contribute through a social anthropological proposal on urban behavior today in vogue, and the economic, social, cultural capital in the Puno region. The purpose was to analyze the elements that make up the urban behavior of the inhabitants and the Economic, Social, Cultural capital today. To this end, the documentary design and the qualitative method were used, documents related to the topic of the research and selected at the discretion of the researcher were analyzed, and semi-structured interviews were also applied to 13 representatives of the same number of provinces in the Puno region. The results revealed that in the Puno region the population dynamics tend towards the growth of the city and the abandonment of the countryside, which is caused by bad government policies in relation to rural spaces, also the authorities differentiate rural areas and city areas through the recognition of the population in terms of access to education, to economic participation. Pollution and the lack of economic diversification are the reasons that have ended up shaping the urban image of the Puno region, the response to these problems, being a region with centralized services and that redefined human development, both epistemologically and geographically, and as a consequence the reinterpretation of coexistence. of social groups and the perception of traditions and customs.